Assessment of e-learning readiness in South African schools - Kolo, Ditlalane Irene (Vaal University of Technology, 2019)
The delivery of education and/or curriculum is shifting from the traditional method of delivery to a digital format, most notably the e-learning, using available technology. However, without e-learning readiness, e-learning benefits will not be reaped and the probability of failure in adopting e-learning will be high. Therefore, it is imperative to know the levels of readiness for e-learning of educators and learners in South African schools. In this study, e-learning readiness of the South African educators and learners in previously disadvantaged schools in Gauteng were investigated. A twenty-nine (29) item questionnaire was used to obtain the data. This new learning method is being introduced and will be implemented by Gauteng Department of Education. The data obtained from the questionnaires was then analyzed by using a STOPE (Strategy, Technology, Organization, People and Environment) model. The results obtained by using STOPE analysis indicated the overall readiness for e-learning at a level of 77%. This is above the mid-point of 50% showing that the schools in Gauteng are ready for adoption of e-learning. The five-point Likert scale method was also used to check the e-learning readiness and established a level of 3.86. The schools in Gauteng that participated in our study are ready for e-learning adoption but need to improve on their people and content readiness. These schools show that they will benefit in adopting e-learning in their schools.
M. Tech. (Department of Information and Communication Technology, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Assessment; e-learning; Readiness; Educators; Learners; Dissertations, Academic -- South Africa.; Computer -- Assisted instruction.; Internet in education.; Education -- South Africa.